Rasio Legis Kewenangan Mahkamah Agung Terkait Permohonan Uji Pendapat Keputusan Dewan Perwakilan Rakyat Daerah (Studi Putusan Mahkamah Agung Nomor 02/P/KHS/2020) - Shalahudddin Serba Bagus; Rusydi Rusydi; Sholihan Sholihan; Sri Kusdiantinah (Universitas Islam Darul Ulum Lamongan, 2024)
Law Number 23 of 2014 concerning Regional Government places the Regional People's Representative Council (DPRD) of the district as the organizing element of Regional Government. In carrying out its duties, authorities, and functions, the District DPRD has the right to interpolate, questionnaire, and express opinions. Implementing these three rights is related to the thought that the policies of the regent or local government will have a broad impact on the lives of the community and regions and are contrary to the provisions of laws and regulations.The purpose of this study is to examine the authority of the Supreme Court to conduct an opinion test on the DPRD Decision against the Regional Head and how the process of requesting a DPRD opinion test until the determination of the final decision (Supreme Court decision). This research is a normative legal research using a statutory, concept, and case approach. The collection of legal materials is carried out by conducting literature research. Legal materials are analyzed by quoting and reviewing relevant articles of laws and regulations. In contrast, the opinions of scholars quoted are then used as a theoretical basis to answer research questions.Based on the discussion results on the legal issues raised, it can be concluded that the Supreme Court has the authority to review the opinion of the DPRD. It can be taken as an example in the opinion test of the Jember Regency DPRD; the Supreme Court stated that it rejected the Jember Regency DPRD Decree Number 08 of 2020 because it was not supported by data on the submission of the Regent's Opinion in the forum of interpellation rights and questionnaire rights and administrative violations of governance in the field of personnel. The Jember Regent had followed up the preparation of regional apparatus institutions.